2012
DOI: 10.1002/pbc.24372
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion for adolescent childhood leukemia survivors: Building on prevention science and ehealth

Abstract: Teenage survivors of childhood acute lymphoblastic leukemia (ALL) have increased morbidity likely due to their prior multicomponent treatment. Habits established in adolescence can impact individuals’ subsequent adult behaviors. Accordingly, healthy lifestyles, avoiding harmful actions, and appropriate disease surveillance are of heightened importance among teenage survivors. We review the findings from prevention science and their relevance to heath promotion. The capabilities and current uses of eHealth comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 90 publications
1
26
0
2
Order By: Relevance
“…The reach of the internet in communicating health information to young people is vast and online platforms of communication are increasingly becoming an effective means of facilitating social support in efforts to promote healthy lifestyle behaviors among this hard to reach population. 47,48 Websites and mobile applications (apps) have emerged as promising and innovative approaches to remote intervention delivery. Previous studies of the internet features most desired by TYA cancer survivors found that young people want websites that contain both age appropriate cancer specific information and opportunities to communicate with other cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The reach of the internet in communicating health information to young people is vast and online platforms of communication are increasingly becoming an effective means of facilitating social support in efforts to promote healthy lifestyle behaviors among this hard to reach population. 47,48 Websites and mobile applications (apps) have emerged as promising and innovative approaches to remote intervention delivery. Previous studies of the internet features most desired by TYA cancer survivors found that young people want websites that contain both age appropriate cancer specific information and opportunities to communicate with other cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Second, health behaviors such as smoking and excessive alcohol consumption are equally well-established risks of malignancy. They have been associated with higher burdens of late morbidity and secondary malignancy among childhood and adult cancer survivors [36,37]. It is therefore quite possible that AYA health behaviors during and after treatment play an important role in later risk.…”
Section: Discussionmentioning
confidence: 99%
“….) auprès de ce public [32,45,46]. Ces outils paraissent également intéressants pour le soutien social et le partage d'expériences nécessaire au renforcement de la motivation et au changement de comportement et ouvrent des perspectives de recherche interdisciplinaire innovantes.…”
Section: Discussionunclassified
“…Les auteurs estiment que le manque de connaissance sur les effets à long terme des traitements associés à des comportements à risque de cancer ne permet pas un engagement de ces jeunes dans des comportements de santé. Un article de synthèse d'Elliot et al s'est intéressé à la promotion de la santé chez les enfants, adolescents et jeunes adultes ayant eu un cancer, par le biais des nouveaux supports technologiques sur Internet (« e-health »), et souligne la pertinence de s'appuyer sur ces nouvelles technologies pour la diffusion et la promotion de comportement de prévention de la santé [32]. …”
Section: Promotion De La Santéunclassified